Systemic Endothelial Function in Primary Open-Angle Glaucoma - Mustafa Atas; Hasan Basri Arifoglu; Arzu Seyhan Karatepe Hashas; Bahadır Sarli; Suleyman Demircan; Ayse Ozkose; Altan Goktas (Journal of Ophthalmology, 2014)
Objective. We aimed to assess peripheral vascular endothelial function in open-angle glaucoma (POAG) by measuring flow-mediated dilatation (FMD). Materials and Methods. The study included 20 cases with POAG (group 1, mean age 58.68±13.3 years) and 30 healthy individuals (group 2, mean age 58.68±13.6 years). In all cases, responses of endothelial function were assessed by a cardiologist through measurement of FMD following brachial artery occlusion. Results. Mean percent of FMD, an indicator of endothelial function, was found to be 11.9±4.2% in group 1 and 12.3±4.4% in group 2 (P=0.86). Conclusion. No impairment in systemic vascular function of cases with POAG suggests that POAG could be a local disorder rather than being a component of systemic disease.